Development of a validated short‐form of the Childhood Atopic Dermatitis Impact Scale, the CADIS‐SF15. (15th May 2020) - Gabes, M.; Chamlin, S.L.; Lai, J.‐S.; Cella, D.; Mancini, A.J.; Apfelbacher, C.J.
Abstract: Background: The Childhood Atopic Dermatitis Impact Scale (CADIS) with 45 items may be burdensome to complete. We therefore aimed to develop a CADIS short‐form. Methods: Parents of 300 children completed the prototype CADIS. Exploratory factor analysis was conducted on the 45‐item CADIS version. The most representative items were chosen. Confirmatory factor analysis was used to confirm the a priori factor structure. Content validity was assessed in a focus group of patients, parents, clinicians, methodologists and industry delegates. Internal consistency, 48‐h test–retest reliability, construct validity and responsiveness of the newly developed short‐form were assessed. Results: A total of 270 families provided data at baseline, 34 after 48 h and 228 after 4 weeks. Fourteen items of three different factors fulfilled the proposed eligibility criteria and were included in the draft short‐form. After the content validity rating, one item relating to the child's sleep was added to further improve content validity. The confirmatory factor analyses showed good model fit, and a 15‐item short‐form was initiated, the CADIS‐SF15. The total scale and the three domains showed good internal consistency and test–retest reliability. The correlation between SCORAD and other subjective measures was consistent with our hypotheses. Differences in scores between mild, moderate and severe AD patients were significant, and the CADIS‐SF15 was able to detect changes in 'improving' patients over time. Conclusion: The CADIS‐SF15 with 15 items in three domains is an internally consistent, reliable, valid, responsive and brief measure of QoL in children affected with AD and their parents. Further evaluation of clinical applicability is required.